WILLIAM CHILLINGWORTH AND THE ORIGINS OF ANGLO-AMERICAN PHILOSOPHY OF RELIGION - Sweet, William (Science et Esprit, 2024)
In this paper I look at one of those thinkers who set the stage for, and influenced, Locke and Hume, William Chillingworth (1602-1644), and show how he understood faith, reason, and the relation between the two. Addressing the question of how the relation of faith and reason came to be an issue in the Anglo-American theological and philosophical traditions will provide some context for the later discussions by Locke and Hume on this relation, but will also show the distinctiveness of this earlier account of faith and reason – an account which may provide some insight and resources for discussing the general issue of the relation of faith and reason today.